Pentingnya Pelatihan Kerjasama Tim dalam Mencapai Tujuan Organisasi - Shierli Wijaya (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2024)
This activity aimed to enhance communication and collaboration among employees of PT Summarecon Serpong. The teamwork training was designed to build a solid team, boost work motivation, and optimize the achievement of organizational goals. The methods used included lectures, group discussions supported by PowerPoint and video presentations, and group games to create an engaging atmosphere. Employees were encouraged to ask questions and share challenges related to teamwork. After the discussions, group games were held to boost morale. Participants were divided into four groups, each consisting of seven members. The activity was conducted on Friday, November 10, 2023, at Pradita University, with 28 participants. Based on the pre-test results involving 15 employees, their initial understanding of the importance of teamwork was limited. However, the post-test indicated increased awareness and motivation among employees to apply teamwork in their tasks.